Safety Culture and Risk Management in Agriculture : Sacurima Cost Action CA16123 Highlights and Conclusions - Leppälä, Jarkko; Griffin, Pat; McNamara, John; Rautiainen, Risto (Natural Resources Institute Finland (Luke), 2021)
Agriculture is one of the most hazardous industries in the European Union (EU. Statistics and studies show great differences in national injury and illness rates, as well as approaches and support systems for the prevention of these adverse outcomes. Only a few successful interventions have been found in systematic reviews. Understanding the determinants of safety culture is generally poor and consequently there is generally a lack of well-informed actions to improve health, safety and risk management. This COST Action explored the reasons why agriculture lags behind other sectors, and why some countries have been more successful than others in reducing agricultural injuries and illnesses. The Sacurima COST Action had five active Working Groups (WGs 1–5), eight short term scientific missions, several conference presentations and one training school to address different aspects of the topic. WG1 explored health and safety programmes and approaches on the national level. WG2 identified knowledge, attitudes, behaviours and priorities among farmers in relation to safety, health and risk management. WG3 identified vulnerable populations and measures for training and integrating vulnerable workers safely into the agricultural workforce. WG4 explored EU and national statistics and the means & indicators for monitoring progress. WG5 produced policy recommendations to inform and guide EU and national initiatives and efforts. The policy recommendations were discussed at meetings with various stakeholders and communicated to policy makers, the scientific community, administrative and insurance personnel, farmers and practitioners working towards better social sustainability and safety culture in agriculture. The policy recommendations presented by the Sacurima COST Action were to 1. Integrate Occupational Safety and Health (OSH) into current and future agricultural policies, 2. Establish a European Network for agriculture safety and health, 3. Allocate specific funding for Agriculture OSH research in Horizon 2020/Horizon Europe, 4. Develop and implement OSH education and skills programmes for farmers and workers in the agriculture sector and 5. Improve statistics to reflect the true levels of agricultural workplace fatal and non-fatal injury and ill health.
Keywords: agriculture; Safety; Health; Safety Culture; risk management